2021
DOI: 10.1002/ece3.8422
|View full text |Cite
|
Sign up to set email alerts
|

Comparative riverscape genomics of the rainbow darter (Etheostoma caeruleum) in glaciated and unglaciated environments

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Post‐glacial expansion might result in reduced genetic variation either because of population bottlenecks during recolonization or genetic drift in small refugial populations prior to expansion. Previous smaller studies of the ecologically similar rainbow darters ( E. caeruleum ) as well as other fishes have shown that species with ranges that span glaciated and unglaciated areas have lower genetic diversity in glaciated areas compared to unglaciated areas (Bernatchez & Dodson, 1991; Billington & Hebert, 1991; Haponski & Stepien, 2008; Hewitt, 1996, 2000; Luiken et al, 2021; Sepulveda‐Villet et al, 2009; Sepulveda‐Villet & Stepien, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post‐glacial expansion might result in reduced genetic variation either because of population bottlenecks during recolonization or genetic drift in small refugial populations prior to expansion. Previous smaller studies of the ecologically similar rainbow darters ( E. caeruleum ) as well as other fishes have shown that species with ranges that span glaciated and unglaciated areas have lower genetic diversity in glaciated areas compared to unglaciated areas (Bernatchez & Dodson, 1991; Billington & Hebert, 1991; Haponski & Stepien, 2008; Hewitt, 1996, 2000; Luiken et al, 2021; Sepulveda‐Villet et al, 2009; Sepulveda‐Villet & Stepien, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Fish from previously glaciated basins showed strong genetic (Bernatchez & Dodson, 1991;Billington & Hebert, 1991;Haponski & Stepien, 2008;Hewitt, 1996Hewitt, , 2000Luiken et al, 2021;Sepulveda-Villet et al, 2009;Sepulveda-Villet & Stepien, 2012). Fish from the unglaciated region of Ceasia included at least four recognized species (E. spectabile, E. burri, E. uniporum, and E. pulchellum).…”
Section: Discussionmentioning
confidence: 99%